PENGGUNAAN DOLOMIT (MgCa(CO3)2) SEBAGAI PENSTABIL PH PADA KOMPOSTING SAMPAH DAPUR BERBASIS DEKOMPOSISI ANAEROB DAN AEROB - Anita Dewi Moelyaningrum; Ellyke Ellyke; Rahayu Sri Pujiati (Jurnal Ilmu Kesehatan Masyarakat, 2013)
Composting is one way to reduce waste and add something beneficial to the earth and health. It is very important to analyze the quality of compost before adding compost to the soil. pH value is one of the indicator of compost quality. The pH value is an indicator of the acidity or alkalinity of the maturity compost. The objective of this reseach is to analyzed pH value compost which added dolomit and whithout dolomit, compos quality and reduce waste. Anaerobic and aerobic composter modification from reuse plastic mineral drinking water 19 litter. The method of this research is experimental design.The row organic materials are 3 kg kithcen waste, fruits waste 1 kg (composter anaerobic 1 and aerobic 3) as control and added dolomit 0,3 kg (composter anaerobic 2 and aerobic 4 ) as treatment. The row material in the control and treatment showed that temperature at 20.2 °C and 25°C; pH value at 4.3 and 5.6; moisture at 86.3 and 88.9; carbon into nitrogen (C/N) ratios 23.4 and 14.05.  Maturity compost showed temperature and pH value are at 20°C and 6.0  (composter 3) and at 2.5 °C and 7 (composter 4). Compost Quality analyzed in NPK. The control showed NPK at 0,41; 0.1758; 0,125  (composter 1); 1.42; 0.208; 0.151 (composter 3). The treatment showed NPK at 0.97; 0,0502; 0.124 (composter 2); 1,04; 0.082; 0,222 (composter 4). Waste reduction at 93% (composter 1), 95% (composter 2), 60% (composter 3), 96,8%(composter 4). Dolomit is pH stabilitation on household waste and Effective to redue waste.   Keyword: Dolomit, composting, pH